Discourse versus praxis: European union, policies and human (i) legal status - Campina, Ana (2019)
One of the most powerful instrument to the politic, juridical and judicial and society life is the Discourse. This is the origin and the consequence in the human beings / citizens life, behavior and “position” facing the different contexts. The European Union being an Organization where the Human and Fundamental Rights are in the top of all legally stated actions, within internal or international context, it´s proved that there are serious and different gaps between the official discourse and the effective praxis with prejudice to the promotion, protection and defending the European citizens as the migrants or refugees. The European policies and laws are enough to prevent violations and actions against the supposed protection, but the violation is constant. Portugal is a study case as we assisted to an important evolution, but, there are integration passivity or social absence action of the migrants.